A248 WHAT IS THE MINIMUM TRAINING STANDARD FOR POINT OF CARE INTESTINAL ULTRASOUND? A SINGLE CENTER, PROSPECTIVE, OBSERVATIONAL STUDY TO DEFINE TRAINING STANDARDS. (26th February 2020) - Hansen, T; Baraty, B; Lu, C; Tanyingoh, D; Maaser, C; Novak, K L
Abstract: Background: Higher demands for colonoscopy and magnetic resonance imaging (MRI) for long term disease monitoring can be expected as the prevalence of IBD continues to rise in Canada. As resources are perpetually constrained, timely access to effective monitoring strategies important to direct care are increasingly compromised. Intestinal ultrasound provides a cost-effective solution to these challenges. Intestinal ultrasound (IUS) is a patient-centered, accurate modality used during clinic by non-radiologists to enhance clinical decision making. Minimum IUS training standards have yet to be established. Aims: The aim of this study is to report a single operator IUS performance characteristics after completion of 4 weeks of training with 100 completed supervised scans. Methods: A single center, prospective, observational study over 4 years utilizing a convenience sample of patients presenting to the inflammatory bowel disease (IBD) clinic at the University of Calgary. A single operator compared IUS to gold standard (either colonoscopy, or alternative cross-sectional imaging) with sensitivity, specificity, positive and negative predictive value calculated for each year. Joinpoint regression was performed to analyze the trend for sensitivity and specificity over the study period. Results: A total of 235 IUS were performed on 235 individuals diagnosed with IBD between 2013 and 2016. There were individuals with 26 ulcerative colitis and 209 persons diagnosed with Crohn's disease. There was a non-significant increase in sensitivity and specificity point estimates over the 4 year period (Table 1). The sensitivity, specificity, positive predictive value, and accuracy of IUS in 2016 were 100% (95% CI: 81%-100%), 92% (95% CI: 62%-100%), 94% (95% CI: 72%-99%) and 97% (95% CI: 8%-100%) respectively. Conclusions: IUS provision by a gastroenterologist having completed 100 supervised scans during training within an expert center is sufficient, resulting in high accuracy. Although there is some improvement over time, the trend towards improvement over time is not significant. This study provides evidence to inform IUS training programs with a minimum training standard benchmark, imperative with expanding demand and development of new expert centers. Funding Agencies: None